Floor plan of Phonse Ducey's twine store, Keels, NL. - Catherwood, Kristin; Millar, Edward; Whitney, Erin (2012)
This building was constructed in the early 1950s, under the supervision of Reg Chapman, as a house for Felix Penny. Phonse Ducey purchased the house to use as his twine store in 1978. The original structure was based on a two room plan (kitchen and bedroom), with a linney containing a small front porch and rear pantry. Phonse opened up the doorway between the former kitchen and bedroom to make more space for net-making. Today, the house is rarely used, but during the time of the cod trap fishery, the space was extensively employed during the winter months, when Phonse and other fishermen would spend many days there making nets and mending those that had been torn during the fishing season.